Coeliac disease: an update for pathologists. Issue 10 (4th October 2006) - Dickson, B C; Streutker, C J; Chetty, R
Abstract : Coeliac disease is the manifestation of an immune hypersensitivity reaction towards gluten and related proteins, in genetically predisposed people. Although the precise pathogenesis of this condition remains to be fully elucidated, it is probably multifactorial in origin. The diagnosis of coeliac disease has traditionally depended on intestinal biopsies alone; nowadays, the diagnosis has been expanded to include an array of serological markers. This review is intended to offer pathologists an update of the relevant history and immunopathology pertaining to coeliac disease and also to offer recommendations on the ongoing responsibilities of the pathologist in the diagnosis and reporting of coeliac disease.